A Conceptual Study of Grahani Roga (Irritable Bowel Syndrome) and its Management Through Dietary Modification - Rawat, Sunita; Singh, Ranweer; Sahu, Preeti; Padhar, Bharat Kumar; Mutha, Rashmi; Meena, HML (International Research Journal of Ayurveda & Yoga, 2022)
Irritable bowel syndrome (IBS) is one of the most frequent yet poorly understood disorders encountered in clinical practise. The symptoms of this illness are long-term, sometimes severe, and frequently do not respond well to treatment, leading in a lower quality of life. More than 40% of new referrals to gastroenterology outpatient clinics are due to IBS. The diagnosis is made using the Rome IV criteria. The aetiology and pathophysiology of this disease are unknown. It can be managed in Ayurveda using the notion of Grahani. The basic Samprapthi is found at the Grahani and Pakwasaya levels, as a result of Agnidushti. IBS has Tridoshaja symptoms with Vata predominance. As a result, medicines that contain Deepana, Pachana, Anulomana, or Grahi qualities are ideal. Because psychological issues are involved, Satwavajaya Chikitsa (psychotherapy) is beneficial. Because it is chronic and relapsing, dietary and lifestyle changes, as well as exercises and relaxation techniques, can help with management. The current article summarises the ayurvedic position on Grahani roga and how to treat it with Ayurvedic principles and a dietary pattern.